NOVEL USE OF AGE-ADJUSTED CHARLSON COMORBIDITY INDEX (ACCI) AS A RISK STRATIFICATION TOOL FOR DEVELOPMENT OF POSTOPERATIVE SARS-COV-2 INFECTION IN SURGICAL PATIENTS - Bhatti, Khalid Munir; Hamzah, Basem; Rehman, Shafiq; Birkett, Emily; Langford, Wren; Aung, Myat; Canelo, Ruben (Journal of Ayub Medical College Abbottabad, 2021)
Background: Current study documents the role of Age adjusted Charlson Comorbidity Index (ACCI) as a stratification tool for the development of postoperative SARS-CoV-2 infection in surgical patients. Methods: This prospective cohort study was conducted over the period of 8 weeks starting on 1st of March 2020. Sampling was convenience and purposive and included all consecutive patients who underwent any surgical procedure. Follow up period was 30 days. Outcomes included postoperative SARS-CoV-2 infection, morbidity and 30-day mortality. Risk factors for development of infection were detected by univariate and multivariate analysis. Results: Postoperative SARS-CoV-2 infection developed in 37 cases while 131cases remained confirmed negative. Of 37 patients, 18 were male while 19 were female. Postoperative complications developed in 17 patients (45.9%). In-hospital 30-day mortality was 16.2% (n=6). The factors that increased the chances of postoperative SARS-CoV-2 infection (p<0·00) included increasing age, higher ACCI Score, emergency surgery, trauma, orthopaedic and vascular procedures, spinal anaesthesia, and surgeries of complex nature. In adjusted analyses, predictors of postoperative infection included ACCI score of 4 or more (5.54 [1·51-20.34], p<0·01), and orthopaedics or vascular procedures versus others (12.32 [1.98-76.46], p<0·007). Based on infection rates across the different scores of ACCI, cohort was divided into 3 groups. ACCI score of zero had postoperative SARS-CoV-2 infection rate of 1.9 % (negative predictive value, 98.1%) compared with 36.26% in patients with score of 4 or more (sensitivity, 89.19%). Conclusion: Low risk surgical patients (ACCI=0) should have universal precautions, while intermediate risk group (ACCI=1-3) should have extra precautions. The options for high-risk patients (ACCI ‰¥4) include cancellation of nonurgent surgery; delaying the surgery till optimization of modifiable factors; or reverse isolation/ shielding in perioperative period if surgery cannot be cancelled.